1989
DOI: 10.1103/physrevlett.63.1942
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of muonic deuterium inD2gas

Abstract: Diffusion of muonic deuterium (yd) atoms in D2 at 300 K was studied at pressures of 0.1-10 bars by measuring the distributions of time intervals between entry of negative muons into the gas and detection of photons emitted upon the arrival of pd atoms at foils spaced along the muon beam axis. The results indicate an approximately Maxwellian velocity distribution with a mean energy of 1.8 ±0.1 eV for the pd atoms, and pd scattering cross sections in agreement with theory.PACS numbers: 36.10.DrKnowledge of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…A Maxwellian kinetic energy distribution was assumed at n"6, with the energy ¹ M being treated as parameter. This assumption is in fair agreement with results from the muonic hydrogen diffusion experiment [23,24], as it was discussed in [17]. Contrary to radiative and Auger processes, the transition energy in Coulomb collisions transforms to the recoil of heavy particles, and a p can gain about 28 eV as a result of transition (n"5) P (n"4) and 61 eV for (n"4) P (n"3).…”
Section: Cascade Processes and Kineticssupporting
confidence: 74%
See 1 more Smart Citation
“…A Maxwellian kinetic energy distribution was assumed at n"6, with the energy ¹ M being treated as parameter. This assumption is in fair agreement with results from the muonic hydrogen diffusion experiment [23,24], as it was discussed in [17]. Contrary to radiative and Auger processes, the transition energy in Coulomb collisions transforms to the recoil of heavy particles, and a p can gain about 28 eV as a result of transition (n"5) P (n"4) and 61 eV for (n"4) P (n"3).…”
Section: Cascade Processes and Kineticssupporting
confidence: 74%
“…By treating the kinetic energy as a fitting parameter and comparing the results for Q Q with the data of [7], they concluded that the average kinetic energy of the p in H/D mixtures is about 6 eV. The experiments on the p and d diffusion in gas [23,24,25], however, demonstrate that the kinetic energy distribution depends on the density and has a multicomponent structure. The mean kinetic energy of muonic hydrogen in the ground state in gas increases from about 2 eV at 47 mbar to more than 9 eV at 750 mbar [25].…”
Section: Introductionmentioning
confidence: 95%
“…[70], and at CERN [71]. Recent experiments at PSI on diffusion of muonic atoms in gaseous targets at very low pressures [72] established that the (d~t)ls atoms approximately follow a Maxwell distribution with a mean energy E= 1.8 0.1eV. This value unexpectedly exceeds previous theoretical estimations [73,49,74,66], all below 1 eV.…”
Section: Thermalization Of Muonic Atomsmentioning
confidence: 92%
“…В дальнейшем мезоатомы замедляются в упругих столкновениях типа и, кроме того, в них происходят неупругие процессы девозбуждения, пу тем внешнего оже эффекта при столкновениях мезоатомов с молекула Вследствие всех этих процессов энергетическое распределение мезо атомов в основном состоянии может отличаться от максвелловского, и это отличие может оказаться существенным при детальном описании кинетики процессов катализа. В последние годы получены экспери ментальные свидетельства в пользу этого заключения [127][128][129].…”
Section: 1unclassified